2020
DOI: 10.3390/atmos11040386
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Analysis of Turbulence Characteristics over the Tropical Western Pacific Based on Radiosonde Data

Abstract: The tropical region is a key area for the interaction between the stratosphere and troposphere. The strong convective activity in the troposphere produces a series of gravity wave activities, which result in strong and widespread turbulence over the region. Therefore, studying the turbulent activity in the western Pacific is essential for understanding the characteristics of atmospheric disturbance over this region, which has the world’s most complex circulation system. In this paper, we explore the characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…The Thorpe scale (L T ) is calculated by obtaining the root mean square value of the displacement. L T shows the local overturning scale in the atmosphere column (Crawford, 1986;Riley and Erik, 2008) and is related to the Ozmidov scale (L 0 ), which describes turbulence in a stably stratified fluid and can be expressed as follows (He et al, 2020b):…”
Section: Calculation Of the Turbulence And Ozone Parametersmentioning
confidence: 99%
“…The Thorpe scale (L T ) is calculated by obtaining the root mean square value of the displacement. L T shows the local overturning scale in the atmosphere column (Crawford, 1986;Riley and Erik, 2008) and is related to the Ozmidov scale (L 0 ), which describes turbulence in a stably stratified fluid and can be expressed as follows (He et al, 2020b):…”
Section: Calculation Of the Turbulence And Ozone Parametersmentioning
confidence: 99%
“…The reason is that in monsoon, the maximum values of turbulence parameters (turbulent scale, turbulent energy dissipation rate and turbulent diffusion coefficient) are concentrated at 14–16 km, and the IGWs extracted in this paper avoid the height interval near the tropopause. Therefore, the significant enhancement of turbulent activity in this area has no clear relationship with the activity of the IGW extracted in the troposphere, but is due to strong wind shear and static instability (He, Sheng, Zhou, et al., 2020).…”
Section: Conclusion and Summarymentioning
confidence: 99%
“…In previous work, statistical analysis has been carried out on the characteristics of turbulence activity in the Western Pacific (He, Sheng, Zhou, et al., 2020), and it is found that turbulence mainly occurs in the middle and upper troposphere (10–16 km), with thermal and shear instability co‐existence. At the same time, the turbulent activity near the tropopause forms a “strongest mixing zone”, which is strengthened from July to September (monsoon), while the turbulent activity of the corresponding season is significantly weaker in the middle and lower troposphere compared with other seasons.…”
Section: Conclusion and Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…In turn, precipitation can be predicted to a certain extent through changes in atmospheric turbulence. It is of great significance to improve the accuracy of weather forecast and numerical weather model (He et al, 2020b).…”
Section: Introductionmentioning
confidence: 99%